TAHAPAN PERKEMBANGAN SENI RUPA ANAK USIA DINI - Saripah (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
Art education as a form to shape the attitude and personality of children who have mental functions which include fantasy, sensitivity, creativity and expression. A child can fantasize about his work, through the feeling of the child pouring his ideas into the work, making the child sensitive, making the child have good creativity, and expressing the work of art. From an early age children have enormous potential. At this time children experience very rapid intellectual brain development. Children are able to absorb quickly every incoming stimulus. Children will be able to memorize a lot of information such as vocabulary, tones, sounds and so on. Therefore, if parents squander a golden opportunity in childhood, it means they are missing a very good moment to provide a foundation for the next child's education. One of the efforts that can be made to express intellectual power combined with the power of imagination is through visual arts.